Whole-Genome Mapping Reveals Novel QTL Clusters Associated with Main Agronomic Traits of Cabbage (Brassica oleracea var. capitata L.) - Lv, Honghao; Wang, Qingbiao; Liu, Xing; Han, Fengqing; Fang, Zhiyuan; Yang, Limei; Zhuang, Mu; Liu, Yumei; Li, Zhansheng; Zhang, Yangyong (Frontiers in Plant Science, 2016)
We describe a comprehensive quantitative trait locus (QTL) analysis for 24 main agronomic traits of cabbage. Field experiments were performed using a 196-line double haploid population in three seasons in 2011 and 2012 to evaluate important agronomic traits related to plant type, leaf, and head traits. In total, 144 QTLs with LOD threshold > 3.0 were detected for the 24 agronomic traits: 25 for four plant-type-related traits, 64 for ten leaf-related traits, and 55 for ten head-related traits; each QTL explained 6.0–55.7% of phenotype variation. Of the QTLs, 95 had contribution rates higher than 10%, and 51 could be detected in more than one season. Major QTLs included Ph 3.1 (max R2 = 55.7, max LOD = 28.2) for plant height, Ll 3.2 (max R2 = 31.7, max LOD = 13.95) for leaf length, and Htd 3.2 (max R2 = 28.5, max LOD = 9.49) for head transverse diameter; these could all be detected in more than one season. Twelve QTL clusters were detected on eight chromosomes, and the most significant four included Indel481–scaffold18376 (3.20 Mb), with five QTLs for five traits; Indel64–scaffold35418 (2.22 Mb), six QTLs for six traits; scaffold39782–Indel84 (1.78 Mb), 11 QTLs for 11 traits; and Indel353–Indel245 (9.89 Mb), seven QTLs for six traits. Besides, most traits clustered within the same region were significantly correlated with each other. The candidate genes at these regions were also discussed. Robust QTLs and their clusters obtained in this study should prove useful for marker-assisted selection in cabbage breeding and in furthering our understanding of the genetic control of these traits.